Unitary colligations and parametrization formulas - Arocena, R. (Український математичний журнал, 1994)
This paper aims to describe, in a rather sketchy but relatively selfcontained way, some relations between the unitary colligations, which are regarded as linear systems, and the parametrization formulas for the solutions of some interpolation problems. Наведено опис деяких співвідношень між унітарними операторними вузлами, які розглядаються як лінійні системи, та формулами параметризації для розв'язків деяких інтерполяційних задач.